2011
DOI: 10.1016/j.snb.2011.09.079
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of the selectivity enhancement obtained by using smart hydrogels that are zwitterionic when detecting glucose with boronic acid moieties

Abstract: Because the boronic acid moiety reversibly binds to sugar molecules and has low cytotoxicity, boronic acid-containing hydrogels are being used in a variety of implantable glucose sensors under development, including sensors based on optical, fluorescence, and swelling pressure measurements. However, some method of glucose selectivity enhancement is often necessary, because isolated boronic acid molecules have a binding constant with glucose that is some forty times smaller than their binding constant with fruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 49 publications
1
36
0
Order By: Relevance
“…This property had been attributed to the formation of reversible crosslinks in the hydrogels with glucose. However, Horkay and Magda and co-workers 200 have shown that changes in the thermodynamic mixing interactions between polymer network and solvent are the most important factors controlling swelling and shrinking of the hydrogels.…”
Section: Polymers For Sensing Applicationsmentioning
confidence: 99%
“…This property had been attributed to the formation of reversible crosslinks in the hydrogels with glucose. However, Horkay and Magda and co-workers 200 have shown that changes in the thermodynamic mixing interactions between polymer network and solvent are the most important factors controlling swelling and shrinking of the hydrogels.…”
Section: Polymers For Sensing Applicationsmentioning
confidence: 99%
“…Novel research, establishing spectroscopic evidence for glucose–bis (boronate) crosslinks formed in hydrogels, was proposed by Magda and co‐workers . They fabricated a zwitterionic hydrogel via copolymerization of glucose‐responsive hydrogels, including boronic acid, with tertiary amines (Lewis bases).…”
Section: Glucose‐responsive Hydrogelsmentioning
confidence: 99%
“…In addition, the properties of a polymer such as the number of charged groups, density of crosslinking, monomer distribution, and chemical quality play key roles in the dynamic characteristics. For example, using a low concentration of tertiary amines in a boronic acid hydrogel was found to highly increase glucose selectivity and cause hydrogel shrinkage in response to glucose addition …”
Section: Glucose‐responsive Hydrogelsmentioning
confidence: 99%
“…To introduce the reversible glucose‐sensing property, we selected the BA‐containing compound and conjugated it to the HC NG. BA is known to be highly selective and sensitive for the cis ‐diol on glucose and has reproducible and stable reversible binding properties . There have been many studies of the application of BA for glucose sensing using various methods, including colorimetric, fluorescent, or electrochemical changes, but many problems remain, such as photochemical instability and particular difficulty in electrical connections …”
Section: Introductionmentioning
confidence: 99%
“…BA is known to be highly selective and sensitive for the cis -diol on glucose and has reproducible and stable reversible binding properties. [ 8,25,26 ] There have been many studies of the application of BA for glucose sensing using various methods, including colorimetric, fl uorescent, or electrochemical changes, but many problems remain, such as photochemical instability and particular diffi culty in electrical connections. [ 9,[27][28][29][30] We designed compact polymeric nanoparticles of HA (modifi ed by hydrophobic cholesterol and phenylboronic acid) as a guest material for MWNT yarn, and then utilized their reversible swelling/ deswelling for yarn actuation.…”
Section: Introductionmentioning
confidence: 99%